Synthesis, structure and properties of some 5-R-4-phenyl-1,2,4- triazole-3-thiol derivatives - Hotsulia, A. S.; Гоцуля, Андрій Сергійович; Гоцуля, А. С. (Запорізький державний медичний університет, 2019)
Pyrrole, 1,2,4-triazole and indole derivatives belong to the group of aza-heterocyclic compounds, which have been associated with significant advances in the development of new drugs. Combining these heterocycles in one molecule increases the likelihood of detecting among these compounds substances with a certain kind of biological activity. The aim of the work was to optimize the conditions of synthesis and study the properties of S-alkylderivatives of 5-R-4-phenyl-1,2,4- triazole-3-thiol containing pyrrole and indolpropane fragments in their structure. Materials and methods. Pyrrole and indole-3-butanoic acid were used as key starting reagents. 4-Phenyl-5-(pyrrol-2-yl)-1,2,4-triazole-3- thiol was obtained by acylation, hydrazinolysis, nucleophilic addition of phenylisothiocyanate followed by intramolecular heterocyclization. For the synthesis of 5-(3-(indol-3-yl)propyl)-4-phenyl-1,2,4-triazole-3-thiol, the reaction of the interaction of the potassium salt of indole- 3-butanoic acid with bromethane was carried out to obtain the appropriate ester. Subsequent stages of chemical conversion included hydrazinolysis reactions, the addition of phenylisothiocyanate, and alkaline cyclization. The structure of the obtained compounds was confirmed by data of elemental analysis, 1H NMR spectroscopy and IR-spectrophotometry. The individuality of substances was established by using high performance liquid chromatography with diode-array and mass spectrometric detection. Results. S-alkylderivatives of 5-(3-(indol-3-yl)propyl)-4-phenyl-1,2,4-triazole-3-thiol and 4-phenyl-5-(pyrrol-2-yl)-1,2,4-triazole-3-thiol has been synthesized and their structure was established and studied physical properties. The synthesized compounds have been subjected to the in silico molecular docking study against the kinases of anaplastic lymphoma by using the 2XP2 ligand, lanosterol 14-α-demethylase by using the 3LD6 ligand, cyclooxygenase-2 by using the ligand which were downloaded from the protein data bank (PDB). Conclusions. Molecular docking has shown the ability of the synthesized compounds to influence the kinase activity of anaplastic lymphoma, cyclooxygenase-2 and lanosterol-14-α-demethylase. Похідні піролу, 1,2,4-тріазолу та індолу належать до групи азагетероциклічних сполук, з використанням яких пов’язані значущі успіхи у сфері створення нових лікарських засобів. Поєднання цих гетероциклів в одній молекулі дає змогу підвищити ймовірність виявлення серед відзначених сполук речовин із певним видом біологічної активності. Мета роботи – оптимізація умов синтезу та дослідження властивостей S-алкілпохідних 5-R-4-феніл-1,2,4-тріазол-3-тіолу, які містять у своїй структурі пірольний та індолпропановий фрагменти. Матеріали та методи. Як ключові вихідні реагенти використали пірол та індол-3-бутанову кислоту. За допомогою реакцій ацилювання, гідразинолізу, нуклеофільного приєднання фенілізотіоціанату з наступною внутрішньомолекулярною гетероциклізацією одержали 4-феніл-5-(пірол-2-іл)-1,2,4-тріазол-3-тіол. Для синтезу 5-(3-(індол-3-іл)пропіл)-4-феніл-1,2,4-тріазол-3-тіолу попередньо провели реакцію взаємодії калієвої солі індол-3-бутанової кислоти з брометаном, що дало змогу одержати відповідний естер. Наступні стадії хімічного перетворення включали реакції гідразинолізу, приєднання фенілізотіоціанату та лужної циклізації. Структура отриманих сполук підтверджена даними елементного аналізу, 1Н ЯМР-спектроскопії та ІЧ-спектрофотометрії. Індивідуальність речовин встановлена за допомогою високоефективної рідинної хроматографії з діодно-матричною та мас-спектрометричною детекцією. Результати. Синтезували S-алкілпохідні 5-(3-(індол-3-іл)пропіл)-4-феніл-1,2,4-тріазол-3-тіолу та 4-феніл-5-(пірол-2-іл)-1,2,4-тріазол-3-тіолу, довели їхню будову та дослідили фізичні властивості. Синтезовані сполуки піддані докінґовим дослідженням in silico для визначення можливого впливу на кіназу анапластичної лімфоми з використанням ліганду 2XP2, ланостерол 14-α-деметилазу з використанням ліганду 3LD6, циклооксигеназу-2 з використанням ліганду 4Z0L, які одержані з Банку даних білків (РDB). Висновки. Молекулярний докінґ показав здатність синтезованих сполук впливати на активність кінази анапластичної лімфоми, ланостерол 14-α-деметилази та циклооксигенази-2. Производные пиррола, 1,2,4-триазола и индола относятся к группе азагетероцикличных соединений, с использованием которых связаны значительные успехи в области создания новых лекарственных средств. Сочетание данных гетероциклов в одной молекуле позволяет повысить вероятность установления среди указанных соединений веществ с определенным видом биологической активности. Цель работы – оптимизация условий синтеза и исследования свойств S-алкилпроизводных 5-R-4-фенил-1,2,4-триазол-3-тиола, содержащих в своей структуре пиррольный и индолпропановый фрагменты. Материалы и методы. В качестве ключевых исходных реагентов использованы пиррол и индол-3-бутановая кислота. С помощью реакций ацилирования, гидразинолиза, нуклеофильного присоединения фенилизотиоцианата с последующей внутримолекулярной гетероциклизацией получен 4-фенил-5-(пиррол-2-ил)-1,2,4-триазол-3-тиол. Для синтеза 5-(3-(индол-3-ил)пропил)-4-фенил-1,2,4-триазол-3-тиола предварительно проведена реакция взаимодействия калиевой соли индол-3-бутановой кислоты с бромэтаном, что позволило получить соответствующий эфир. Следующие стадии химического превращения включали реакции гидразинолиза, присоединение фенилизотиоцианата и щелочной циклизации. Структура полученных соединений подтверждена данными элементного анализа, 1Н ЯМР-спектроскопии и ИК-спетрофотометрии. Индивидуальность веществ установлена с помощью высокоэффективной жидкостной хроматографии c диодно-матричной и масс-спектрометрической детекцией. Результаты. Синтезированны S-алкилпроизводные 5-(3-(индол-3-ил)пропил)-4-фенил-1,2,4-триазол-3-тиола и 4-фенил-5-(пиррол-2-ил)-1,2,4-триазол-3-тиола, доказано их строение и исследованы физические свойства. Синтезированные соединения подвергнуты докинговым исследованиям in silico для определения возможного влияния на киназу анапластической лимфомы с использованием лиганда 2XP2, ланостерол 14-α-деметилазы с использованием лиганда 3LD6, ЦОГ-2 с использованием лиганда 4Z0L, которые получены из Банка данных белков (РDB). Выводы. Молекулярный докинг продемонстрировал возможность синтезированных соединений влиять на активность киназы анапластической лимфомы, ланостерол 14-α-деметилазы и циклооксигеназы-2.
Синтез, будова та властивості деяких похідних 5-R-4-феніл-1,2,4-тріазол-3-тіолу
Синтез, строение и свойства некоторых производных 5-R-4-фенил-1,2,4-триазол-3-тиола
Keywords: pyrrole; 1,2,4-triazole; indole; physical-chemical properties; molecular docking; 1,2,4-тріазол; пірол; індол; фізико-хімічні властивості; молекулярний докінґ; пиррол; 1,2,4-триазол; индол; физико-химические свойства; молекулярный докинг